Carbon-doped enhanced plasticity high-entropy alloy and preparation method thereof
Patent Information
- Application Number
- CN202410572911.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-10
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-05-10
AI Technical Summary
[0005]基于以上考虑,本发明针对现有面心立方结构单相高熵合金屈服强度普遍很低以及添加C元素强化后塑性容易显著降低的问题,提供一种碳掺杂增强增塑的高熵合金及其制备方法
本发明所制备的碳掺杂增强增塑的高熵合金,制备过程简单可控,加工成本和难度低。其面心立方结构基体相的体积分数超过90%的组织特征保证了其在室温下呈现出优异的塑性,此外,该合金兼具添加C元素所引入的间隙固溶强化和析出强化效应对强度的提升作用,以及相变诱导塑性和/或孪晶诱导塑性效应对加工硬化能力和塑性的提升作用,实现了高强度和高塑性的良好结合。其屈服强度超过250MPa,抗拉强度超过800MPa,断裂延伸率超过40%,在汽车发动机零部件、海底管道、油井设备等领域具有广泛的应用前景。
Smart Images

Figure CN118326225B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of high-entropy alloy materials technology, specifically relating to a carbon-doped reinforced and plasticized high-entropy alloy and its preparation method. Background Technology
[0002] High-entropy alloys are a class of alloys characterized by multiple principal elements. Unlike traditional alloys that contain only one or two main elements, high-entropy alloys are designed by mixing multiple elements at high concentrations, i.e., containing multiple principal elements. This unique concept provides ample room for the design of alloy composition and microstructure. Among the many high-entropy alloy systems, face-centered cubic single-phase high-entropy alloys with low stacking fault energies have received the most attention to date. The deformation mechanism of these alloys can be modulated by changing the stacking fault energy, causing them to generate stress-induced martensite and / or deformation twins during deformation, thereby stimulating phase transformation-induced plasticity and / or twin-induced plasticity effects, resulting in high work hardening capacity, plasticity, and fracture toughness. However, it is important to note that although these alloys exhibit excellent plasticity and fracture toughness, their yield strength is generally low, which greatly limits their engineering applications.
[0003] Adding carbon (C) is an important way to improve the yield strength of high-entropy alloys, but dissolved C can lead to a decrease in work hardening capacity and plasticity. Furthermore, carbides are generally brittle, and their abundant precipitation often further reduces plasticity significantly. Therefore, the pressing challenge is how to improve the strength of face-centered cubic single-phase high-entropy alloys by adding C while ensuring that their plasticity is not reduced. Summary of the Invention
[0004] In face-centered cubic (FCC) single-phase CrMnFeCoNi high-entropy alloys, increasing the Co content and / or decreasing the Ni content can lower the stacking fault energy. A sufficiently low stacking fault energy is a prerequisite for the generation of stress-induced martensite and / or deformation twins during deformation. Therefore, this provides an important basis for the compositional design of high-entropy alloys: by rationally adjusting the Co and Ni contents, FCC high-entropy alloys with very low stacking fault energies can be designed, ensuring that the stacking fault energy remains sufficiently low even after the addition of C, thereby guaranteeing the generation of phase transformation-induced plasticity and / or twin-induced plasticity effects during deformation.
[0005] Based on the above considerations, this invention addresses the problems of generally low yield strength and significant reduction in plasticity of existing face-centered cubic single-phase high-entropy alloys by adding C elements, and provides a carbon-doped reinforced and plasticized high-entropy alloy and its preparation method.
[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: The present invention provides a carbon-doped and plasticized high-entropy alloy, wherein the constituent elements and atomic percentages of the high-entropy alloy are: 18%~22% Cr, 18%~22% Mn, 18%~22% Fe, 32%~35% Co, 4%~6% Ni, and 0.4%~2.1% C.
[0007] Preferably, the atomic percentage ratio of Co to Ni in the high-entropy alloy is 5.8 to 8.1, and the atomic percentage ratio of any two of the three elements Cr, Mn, and Fe is 0.8 to 1.3.
[0008] Preferably, the microstructure of the high-entropy alloy comprises a face-centered cubic matrix phase with a volume fraction of not less than 90% and a molecular weight matrix phase with a volume fraction of not more than 10%. 23 C6 precipitate.
[0009] Preferably, the average grain size of the face-centered cubic matrix phase is 10 μm to 90 μm, and the M 23 The average grain size of the C6 precipitate is no higher than 1.5 μm.
[0010] This invention also provides a method for preparing a carbon-doped reinforced and plasticized high-entropy alloy, the method comprising the following steps: S1. Weigh appropriate amounts of pure Cr, pure Mn, pure Fe, pure Co, pure Ni, and pure C with a purity of not less than 99.9% as raw materials, mix them according to the above high-entropy alloying element ratio, and then melt them in a vacuum medium-frequency induction melting furnace to obtain ingots. S2. Cut the ingot wire into plates about 10mm thick, and then homogenize them under argon protection. S3. Heat-through the homogenized sheet material, and then hot-roll it. S4. The hot-rolled sheet is placed under argon protection for solution treatment to complete the preparation of the high-entropy alloy.
[0011] Preferably, the homogenization treatment temperature in S2 is 1100℃, and the homogenization treatment time is 12h.
[0012] Preferably, the heat penetration temperature in S3 is 900℃~1100℃, and the heat preservation time is 30~40min.
[0013] Preferably, the hot rolling process described in S3 is carried out by a twin-roll strip mill for multi-pass rolling, with a deformation of 10-20% per pass and a total deformation of 50-70%. Except for the last pass, each pass of hot rolling is subjected to a furnace heat preservation treatment after completion. The furnace heat preservation temperature is 900℃-1100℃ and the furnace heat preservation time is 4-6 minutes. After the last pass of hot rolling is completed, water quenching is performed.
[0014] Preferably, the solution treatment temperature in S4 is 1000℃~1100℃, and the solution treatment time is 0.5h~4h.
[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The carbon-doped, reinforced, and plasticized high-entropy alloy prepared by this invention has a simple and controllable preparation process with low processing cost and difficulty. Its microstructure, characterized by a face-centered cubic matrix phase volume fraction exceeding 90%, ensures excellent plasticity at room temperature. Furthermore, this alloy combines the strength-enhancing effects of interstitial solid solution strengthening and precipitation strengthening introduced by carbon addition, with the work-hardening and plasticity-enhancing effects of phase transformation-induced plasticity and / or twinning-induced plasticity, achieving a good balance between high strength and high plasticity. Its yield strength exceeds 250 MPa, tensile strength exceeds 800 MPa, and elongation at break exceeds 40%, making it promising for applications in automotive engine parts, subsea pipelines, and oil well equipment. Attached Figure Description
[0016] To more clearly illustrate the technical solutions of the embodiments of this disclosure, the accompanying drawings of the embodiments will be briefly described below. It should be understood that the drawings described below only relate to some embodiments of this disclosure and are not intended to limit this disclosure, wherein: Figure 1 These are electron backscatter diffraction (EBSD) analysis results of the initial microstructure of the high-entropy alloys prepared in Examples 1-3 of this invention.
[0017] Figure 2 These are the room temperature tensile stress-strain curves of the high-entropy alloys prepared in Examples 1-3 and Comparative Example 1 of this invention.
[0018] Figure 3 These are transmission electron microscope (TEM) images of the microstructures of the high-entropy alloys prepared in Examples 1-3 of this invention.
[0019] Figure 4 These are scanning electron microscope (SEM) images of the initial and deformed microstructures of the high-entropy alloy prepared in Comparative Example 1 of this invention. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of the embodiments of this disclosure clearer, the technical solutions of the embodiments of this disclosure will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this disclosure. All other embodiments obtained by those skilled in the art based on the described embodiments of this disclosure without creative effort are also within the scope of protection of this disclosure.
[0021] Unless otherwise defined, all terms used herein (including technical and scientific terms) shall have the same meaning as commonly understood by one of ordinary skill in the art to which this subject matter pertains. It will be further understood that terms such as those defined in commonly used dictionaries shall be interpreted as having meanings consistent with their meanings in the context of the specification and in the relevant art, and shall not be interpreted in an idealized or overly formal form unless otherwise explicitly defined herein.
[0022] The term "embodiment" as used herein means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of the phrase "embodiment" in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0023] This invention provides a carbon-doped, reinforced, and plasticized high-entropy alloy, wherein the preferred constituent elements and atomic percentages of the high-entropy alloy are: 18%~22% Cr, for example, it can be 18%, 19.85%, 20.36%, 21%, 22%, etc.; 18%~22% Mn, for example, it can be 18%, 19.70%, 20.59%, 21%, 22%, etc.; 18%~22% Fe, for example, it can be 18%, 19%, 20%, 21%, 22%, etc.; 32%~35% Co, for example, it can be 32%, 33.18%, 34%, 35%, etc.; 4%~6% Ni, for example, it can be 4%, 4.5%, 5.33%, 5.7%, 6%, etc.; 0.4%~2.1% C, for example, it can be 0.4%, 0.5%, 0.7%, 0.9%, 1.1%, 1.5%, 1.7%, 1.9%, 2.1%, etc.
[0024] In this invention, when the content of C element is too low, on the one hand, the interstitial solid solution strengthening effect and / or precipitation strengthening effect of C element cannot be fully utilized, so that the alloy cannot obtain high strength. On the other hand, the improvement of stacking fault energy of high-entropy alloy is limited, and the deformation mechanism of low stacking fault energy high-entropy alloy cannot be effectively regulated, thus failing to effectively improve the plasticity of high-entropy alloy. On the other hand, when the content of C element is too high, a large number of carbides will precipitate in high-entropy alloy, resulting in a decrease in the plasticity of high-entropy alloy.
[0025] In this invention, the atomic percentage ratio of Co to Ni in the high-entropy alloy is preferably 5.8 to 8.1, for example, it can be 5.8, 6.19, 6.4, 7.1, 7.5, 7.8, 8.1, etc. The atomic percentage ratio of any two of the three elements Cr, Mn, and Fe is preferably 0.8 to 1.3, and the average percentage ratio is preferably 0.9 to 1.2, for example, it can be 0.9 to 1.05, 0.9 to 1.09, 0.9 to 1.15, etc.
[0026] In this invention, the microstructure of the high-entropy alloy comprises a face-centered cubic matrix phase with a volume fraction of not less than 90% and an M phase with a volume fraction of not more than 10%. 23 C6 precipitate.
[0027] In this invention, the average grain size of the face-centered cubic matrix phase is preferably 10 μm to 90 μm, for example, it can be 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, etc., where M... 23 The average grain size of the C6 precipitate is no higher than 1.5 μm.
[0028] This invention also provides a method for preparing a carbon-doped reinforced and plasticized high-entropy alloy, the method comprising the following steps: S1. Weigh appropriate amounts of pure Cr, pure Mn, pure Fe, pure Co, pure Ni, and pure C with a purity of not less than 99.9% as raw materials, mix them according to the alloy element ratio, and then melt them in a vacuum medium-frequency induction melting furnace to obtain ingots. S2. Cut the ingot wire into plates about 10mm thick, and then homogenize them under argon protection. S3. Heat-through the homogenized sheet material, and then hot-roll it. S4. The hot-rolled sheet is placed under argon protection for solution treatment to complete the preparation of the high-entropy alloy.
[0029] In this invention, the homogenization treatment temperature is preferably 1100℃, and the homogenization treatment time is preferably 12h. Homogenization treatment at this temperature utilizes the non-uniform composition of the microstructure of the as-cast alloy, ensuring that most of the precipitated carbides are distributed within the grains, and that the precipitated carbides are fine-sized.
[0030] In this invention, the heat penetration temperature is preferably 900℃~1100℃, for example, it can be 900℃, 1000℃, 1100℃, more preferably 1100℃, and the heat preservation time is preferably 30~40min, for example, it can be 30min, 35min, 40min, more preferably 30min.
[0031] In this invention, the hot rolling process is performed using a twin-roll strip mill for multiple passes. The deformation amount of each pass is preferably 10-20%, the average deformation amount is preferably 14-16%, the total deformation amount is preferably 50-70%, and the average total deformation amount is preferably 55-65%, for example, it can be 55%, 58%, 61%, 65%, etc. Except for the last pass, each pass of hot rolling is subjected to a furnace heat preservation treatment. The furnace heat preservation temperature is preferably 900℃-1100℃, for example, it can be 900℃, 1000℃, 1100℃, more preferably 1100℃. The furnace heat preservation time is preferably 4-6 minutes, for example, it can be 4 minutes, 5 minutes, 6 minutes, more preferably 5 minutes. After the last pass of hot rolling is completed, water quenching is performed.
[0032] In this invention, the solution treatment temperature is preferably 1000℃~1100℃, for example, it can be 1000℃, 1050℃, 1100℃, and more preferably 1100℃. When the solution treatment temperature is too low, excessive carbides will precipitate in the initial microstructure of the high-entropy alloy, and face-centered cubic matrix phase grains with a small average size (<10μm) will be formed. Both of these will cause a decrease in the plasticity of the high-entropy alloy. When the solution treatment temperature is too high, it will lead to a significant increase in the average grain size of the face-centered cubic matrix phase in the high-entropy alloy (>90μm), reducing the strength of the high-entropy alloy.
[0033] In this invention, the solution treatment time is preferably 0.5h to 4h, for example, it can be 0.5h, 1h, 2h, 3h, 4h, etc. This ensures the formation of relatively uniform face-centered cubic matrix phase grains and controls the average grain size to be within the range of 10μm to 90μm. Furthermore, it avoids the formation of M... 23 The C6 precipitate grows during the prolonged solution treatment, thus ensuring M 23 The average size of the C6 precipitate is no higher than 1.5 μm.
[0034] When the solution treatment time is too short, the grains in the initial microstructure of the high-entropy alloy do not grow sufficiently, which will lead to excessively high stacking fault energy in the high-entropy alloy, suppressing the phase transformation-induced plasticity and / or twin-induced plasticity effects during deformation, thereby reducing the plasticity of the high-entropy alloy; when the solution treatment time is too long, it will promote the formation of excessively large (over 1.5 μm) M-shaped grains. 23 The C6 precipitate phase resulted in an insignificant precipitation strengthening effect, and the large-sized M... 23 C6 precipitates are prone to cracking during early deformation, reducing the plasticity of high-entropy alloys; on the other hand, they promote the formation of abnormally large grains, reducing the strength and plasticity of high-entropy alloys.
[0035] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments thereof: Example 1
[0036] The constituent elements and atomic percentages of a carbon-doped, reinforced, and plasticized high-entropy alloy are as follows: 20.36% Cr, 21.10% Mn, 19.46% Fe, 33.78% Co, 4.82% Ni, and 0.47% C. The atomic percentage ratio of Co to Ni is 7.01; the atomic percentage ratio of any two of the three elements Cr, Mn, and Fe is 0.92 to 1.09.
[0037] The preparation method of carbon-doped reinforced and plasticized high-entropy alloys includes the following steps: S1. Weigh appropriate amounts of pure Cr, pure Mn, pure Fe, pure Co, pure Ni, and pure C with a purity of not less than 99.9% as raw materials, mix them according to the above alloy element ratios, and then melt them in a vacuum medium-frequency induction melting furnace to obtain ingots. S2. Cut the ingot into plates with a thickness of about 10mm, then homogenize them at 1100℃ for 12 hours under argon protection, and then water-quench them. S3. After homogenization, the plate is heated to 1100℃ for 30 minutes to ensure heat penetration, and then rolled in multiple passes using a twin-roll strip mill. The deformation amount of each pass is 10~20%, and the total deformation amount is 62%. Except for the last pass, each pass is reheated at 1100℃ for 5 minutes after hot rolling. After the last pass is hot rolled, it is water-cooled and quenched. S4. The hot-rolled sheet is placed under argon protection and solution treated at 1100℃ for 2 hours, followed by water quenching.
[0038] The initial microstructure of the high-entropy alloy prepared in this embodiment was characterized using EBSD, as shown in the attached figure. Figure 1 As shown in the figure, the initial microstructure of the high-entropy alloy prepared in this embodiment is 100% face-centered cubic phase, with an average grain size of approximately 82 μm.
[0039] The mechanical properties of the high-entropy alloy prepared in this example were measured according to GB / T 228.1–2010 "Metallic materials, tensile testing—Part 1: Test at room temperature". The results are shown in the appendix. Figure 2 As shown, its yield strength and tensile strength are 263 MPa and 808 MPa, respectively, and its elongation at break is 45.3%.
[0040] The deformed microstructure of the high-entropy alloy prepared in this embodiment was characterized by TEM, as shown in the attached figure. Figure 3 As shown in the figure, during the deformation process, the high-entropy alloy prepared in this embodiment generates stress-induced martensite, exhibiting a phase transformation-induced plasticity effect.
[0041] Example 2
[0042] The constituent elements and atomic percentages of a carbon-doped, reinforced, and plasticized high-entropy alloy are as follows: 19.85% Cr, 20.59% Mn, 20.01% Fe, 33.08% Co, 5.33% Ni, and 1.13% C. The atomic percentage ratio of Co to Ni is 6.21; the atomic percentage ratio of any two of the three elements Cr, Mn, and Fe is 0.96–1.04.
[0043] The preparation method of carbon-doped reinforced and plasticized high-entropy alloys includes the following steps: S1. Weigh appropriate amounts of pure Cr, pure Mn, pure Fe, pure Co, pure Ni, and pure C with a purity of not less than 99.9% as raw materials, mix them according to the above alloy element ratios, and then melt them in a vacuum medium-frequency induction melting furnace to obtain ingots. S2. Cut the ingot into plates with a thickness of about 10mm, then homogenize them at 1100℃ for 12 hours under argon protection, and then water-quench them. S3. The homogenized plate is heated to 1100℃ for 30 minutes to achieve heat penetration, and then rolled in multiple passes using a twin-roll strip mill. The deformation amount of each pass is 10~20%, and the total deformation amount is 59%. Except for the last pass, each pass is subjected to a 1100℃ furnace heat treatment for 5 minutes after hot rolling. After the last pass is hot rolled, water quenching is performed. S4. The hot-rolled sheet is placed under argon protection and solution treated at 1100℃ for 2 hours, followed by water quenching.
[0044] The initial microstructure of the high-entropy alloy prepared in this embodiment was characterized using EBSD, as shown in the attached figure. Figure 1 As shown in the figure, the initial microstructure of the high-entropy alloy prepared in this embodiment consists of a face-centered cubic phase with a volume fraction of 99.06% and an M phase with a volume fraction of 0.94%. 23 The C6 precipitate phase composition is as follows. The face-centered cubic phase has an average grain size of approximately 32 μm, and M... 23 The average size of the C6 precipitate is approximately 0.88 μm.
[0045] The mechanical properties of the high-entropy alloy prepared in this example were measured according to GB / T 228.1–2010 "Metallic materials, tensile testing—Part 1: Test at room temperature". The results are shown in the appendix. Figure 2 As shown, its yield strength and tensile strength are 338 MPa and 929 MPa, respectively, and its elongation at break is 52.6%.
[0046] The deformed microstructure of the high-entropy alloy prepared in this embodiment was characterized by TEM, as shown in the attached figure. Figure 3As shown in the figure, during the deformation process, the high-entropy alloy prepared in this embodiment generates stress-induced martensite and deformation twins, exhibiting phase transformation-induced plasticity and twin-induced plasticity effects.
[0047] Example 3
[0048] The constituent elements and atomic percentages of a carbon-doped, reinforced, and plasticized high-entropy alloy are as follows: 18.63% Cr, 21.05% Mn, 19.85% Fe, 33.18% Co, 5.36% Ni, and 1.93% C. The atomic percentage ratio of Co to Ni is 6.19; the atomic percentage ratio of any two of the three elements Cr, Mn, and Fe is 0.88 to 1.13.
[0049] The preparation method of carbon-doped reinforced and plasticized high-entropy alloys includes the following steps: S1. Weigh appropriate amounts of pure Cr, pure Mn, pure Fe, pure Co, pure Ni, and pure C with a purity of not less than 99.9% as raw materials, mix them according to the above alloy element ratios, and then melt them in a vacuum medium-frequency induction melting furnace to obtain ingots. S2. Cut the ingot into plates with a thickness of about 10mm, then homogenize them at 1100℃ for 12 hours under argon protection, and then water-quench them. S3. The homogenized plate is heated to 1100℃ for 30 minutes and then rolled in multiple passes using a twin-roll strip mill. The deformation of each pass is 10-20%, and the total deformation is 59%. Except for the last pass, each pass is reheated at 1100℃ for 5 minutes after hot rolling. The last pass is then water-cooled and quenched. S4. The hot-rolled sheet is placed under argon protection and solution treated at 1100℃ for 2 hours, followed by water quenching.
[0050] The initial microstructure of the high-entropy alloy prepared in this embodiment was characterized using EBSD, as shown in the attached figure. Figure 1 As shown in the figure, the initial microstructure of the high-entropy alloy prepared in this embodiment consists of a face-centered cubic phase with a volume fraction of 95.02% and an M phase with a volume fraction of 4.98%. 23 The precipitate consists of C6. The face-centered cubic phase has an average grain size of approximately 16 μm, and M... 23 The average size of the C6 precipitate is approximately 0.72 μm.
[0051] The mechanical properties of the high-entropy alloy prepared in this example were measured according to GB / T 228.1–2010 "Metallic materials, tensile testing—Part 1: Test at room temperature". The results are shown in the appendix. Figure 2As shown, its yield strength and tensile strength are 438 MPa and 992 MPa, respectively, and its elongation at break is 53.3%.
[0052] The deformed microstructure of the high-entropy alloy prepared in this embodiment was characterized by TEM, as shown in the attached figure. Figure 3 As shown in the figure, during the deformation process, the high-entropy alloy prepared in this embodiment generates stress-induced martensite and deformation twins, exhibiting phase transformation-induced plasticity and twin-induced plasticity effects.
[0053] Comparative Example 4 The high-entropy alloy provided in this comparative example does not contain carbon. The constituent elements and their atomic percentages are as follows: 20.20% Cr, 19.70% Mn, 20.17% Fe, 34.98% Co, and 4.95% Ni. The atomic percentage ratio of Co to Ni is 7.07; the atomic percentage ratio of any two of the three elements Cr, Mn, and Fe is 0.97 to 1.03.
[0054] The preparation method of high-entropy alloys includes the following steps: S1. Weigh appropriate amounts of pure Cr, pure Mn, pure Fe, pure Co, and pure Ni with a purity of not less than 99.9% as raw materials, mix them according to the above alloy element ratio, and then melt them in a vacuum medium frequency induction melting furnace to obtain ingots. S2. Cut the ingot into plates with a thickness of about 10mm, then homogenize them at 1100℃ for 12 hours under argon protection, and then water-quench them. S3. The homogenized plate is placed at 900℃ for 30 minutes for heat treatment and then rolled in multiple passes using a twin-roll strip mill. The deformation amount of each pass is 10~20%, and the total deformation amount is 70%. Except for the last pass, each pass is subjected to a 900℃ furnace heat treatment for 5 minutes after hot rolling. After the last pass is hot rolled, water quenching is performed. S4. The hot-rolled sheet is placed under argon protection and solution treated at 1100℃ for 1 hour, followed by water quenching.
[0055] The initial microstructure of the high-entropy alloy prepared in this comparative example was characterized by SEM, as shown in the attached figure. Figure 4 As shown in the figure, the initial microstructure of the high-entropy alloy prepared in this comparative example consists of a face-centered cubic phase and a close-packed hexagonal phase. The average grain size of the face-centered cubic phase is approximately 81 μm.
[0056] The mechanical properties of the high-entropy alloy prepared in this comparative example were measured according to GB / T 228.1–2010 "Metallic materials, tensile testing—Part 1: Test at room temperature". The results are attached. Figure 2As shown, its yield strength and tensile strength are 167 MPa and 661 MPa, respectively, and its elongation at break is 33.2%.
[0057] The deformed microstructure of the high-entropy alloy prepared in this comparative example was characterized by SEM, as shown in the attached figure. Figure 4 As shown in the figure, the high-entropy alloy prepared in this comparative example generates stress-induced martensite during deformation, exhibiting a phase transformation-induced plasticity effect.
[0058] Compared to Examples 1-3, although the preparation method and high-entropy alloy composition are similar, the alloy composition of the high-entropy alloy prepared in this comparative example exceeds the composition range protected by this patent application, resulting in significantly lower yield strength, tensile strength, and elongation at break compared to the high-entropy alloys prepared in Examples 1-3. On one hand, the high-entropy alloy prepared in this comparative example does not possess the interstitial solid solution strengthening and precipitation strengthening effects introduced by adding C, leading to lower strength. On the other hand, the initial microstructure of the high-entropy alloy prepared in this comparative example has a face-centered cubic phase volume fraction of less than 90%, and introduces a close-packed hexagonal phase with lower plasticity, resulting in lower plasticity.
[0059] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A carbon-doped, reinforced, and plasticized high-entropy alloy, characterized in that, The high-entropy alloy comprises the following elements and atomic percentages: 18%~22% Cr, 18%~22% Mn, 18%~22% Fe, 32%~35% Co, 4%~6% Ni, and 0.4%~2.1% C; the atomic percentage ratio of Co to Ni in the high-entropy alloy is 5.8~8.1, and the atomic percentage ratio of any two of the three elements Cr, Mn, and Fe is 0.8~1.3; the microstructure of the high-entropy alloy comprises a face-centered cubic matrix phase with a volume fraction of not less than 90% and a Mn phase with a volume fraction of not more than 10%. 23 C6 precipitate phase; the average grain size of the face-centered cubic matrix phase is 10 μm to 90 μm, the M 23 The average grain size of the C6 precipitate is not higher than 1.5 μm; the high entropy alloy has a yield strength ≥250 MPa, a tensile strength ≥800 MPa, and a fracture elongation ≥40%.
2. The method for preparing a carbon-doped reinforced and plasticized high-entropy alloy according to claim 1, characterized in that, The preparation method includes the following steps: S1. Weigh appropriate amounts of pure Cr, pure Mn, pure Fe, pure Co, pure Ni, and pure C with a purity of not less than 99.9% as raw materials, mix them according to the above high-entropy alloying element ratio, and then melt them in a vacuum medium-frequency induction melting furnace to obtain ingots. S2. Cut the ingot wire into plates about 10mm thick, and then homogenize them under argon protection. S3. Heat-through the homogenized sheet material, and then hot-roll it. S4. The hot-rolled sheet is placed under argon protection for solution treatment to complete the preparation of the high-entropy alloy.
3. The method for preparing a carbon-doped reinforced and plasticized high-entropy alloy according to claim 2, characterized in that, The homogenization treatment temperature in S2 is 1100℃, and the homogenization treatment time is 12h.
4. The method for preparing a carbon-doped reinforced and plasticized high-entropy alloy according to claim 2, characterized in that, The heat penetration temperature described in S3 is 1000℃~1100℃, and the heat preservation time is 30~40min.
5. The method for preparing a carbon-doped reinforced and plasticized high-entropy alloy according to claim 2, characterized in that, The hot rolling process described in S3 uses a twin-roll strip mill for multi-pass rolling, with each pass having a deformation of 10-20% and a total deformation of 50-70%. Except for the last pass, each pass of hot rolling is followed by a furnace heat treatment, with a furnace heat treatment temperature of 1000℃-1100℃ and a furnace heat treatment time of 4-6 minutes. After the last pass of hot rolling, water quenching is performed.
6. The method for preparing a carbon-doped reinforced and plasticized high-entropy alloy according to claim 2, characterized in that, The solution treatment temperature in S4 is 1000℃~1100℃, and the solution treatment time is 0.5h~4h.
Citation Information
Patent Citations
High-strength, high-plasticity, high-crack-tolerance and high-entropy alloy and preparation method thereof
CN116356190A
KR20220001374A